STATUS OF BMI AND MACRO NUTRITION CONDITIONS OF PABSI ATHLETES IN WEST KALIMANTAN PROVINCE AT THE XX PON EVENT PAPUA - Isti Dwi Puspita Wati; Y. Touvan Juni Samodra; Maharani Fatima Gandasari; Ghana Firsta Yosika; Putra Sastaman (STKIP Melawi, 2022)
Adequate food intake is one of the keys that will support athlete performance apart from regular and continuous training. An imbalance in food intake will result in athletes experiencing